Waste is a dirty word in the circular economy. (Research'eu results magazine)
There is an urgent need for new thinking and practices when it comes to reducing the environmental load coming from industry, agriculture and communities, as continuing on the business-as-usual trajectory is widely recognised as unsustainable. An EU-funded project points a way forward not to be so wasteful with our waste.